(Invited) Germanium Enrichment for Planar-, Fin- and Nanowire-Channel MOSFETs Made on SOI. (18th August 2016) - Augendre, Emmanuel; Loubet, Nicolas; Morin, Pierre Francois; Liu, Qing; Schmitt, Joël; L'Herron, Benoît; Nguyen, Phuong; Barraud, Sylvain; Hutin, Louis; Maitrejean, Sylvain; De Salvo, Barbara; Coquand, Rémi; et al.
Abstract : This paper discusses the fabrication of SiGe channel for Ultra-Thin Body and Buried oxide Fully Depleted Silicon-On-Insulator (UTBB FDSOI) MOSFETs, FinFETs and Nano Wire FETs (NWFETs). Enrichment conditions need to be tuned to avoid excessive Ge pile-up on tensile-strained planar Si films due to lower Ge diffusion. Patterning SiGe Fins in thick blanket SiGe layers faces the crystal quality limits set by plastic relaxation beyond critical thickness. As an alternative, Ge enrichment of pre-existing Si Fins requires conformal SiGe growth and can produce strained SiGe Fins up to 50% without significant relaxation, independently from Fin height. Enrichment requirements for NWFETs are identical to those of planar devices. As a result, NWFETs benefit from both SiGe mechanical stability and uniaxial compressive strain performance enhancement.